2004
DOI: 10.1001/archotol.130.7.819
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Recurrent Well-Differentiated Thyroid Carcinoma

Abstract: Background:The AMES (age, distant metastasis, tumor extent, and size), AGES (age, tumor size, histologic grade, tumor extent, distant metastasis), and MACIS (distant metastasis, age, completeness of primary tumor resection, local invasion, and tumor size) prognostic systems for welldifferentiated thyroid carcinoma (WDTC) are well known. The development of disease recurrence is associated with a poor outcome; however, the prognostic importance of multiple treatment failures has not been clearly reported.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 15 publications
8
91
2
Order By: Relevance
“…The mean age at presentation of 44 years and female predominance were also consistent with findings from different international studies [16][17][18]. In contrast, the mean duration of the goiter before initial consult of 6 years and larger mean tumor size reflect the limited access to medical care typical of most patients seen at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…The mean age at presentation of 44 years and female predominance were also consistent with findings from different international studies [16][17][18]. In contrast, the mean duration of the goiter before initial consult of 6 years and larger mean tumor size reflect the limited access to medical care typical of most patients seen at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…Although WDTC is the most common type of thyroid carcinoma, it is the only type of this carcinoma with a low mortality rate (15)(16)(17) and increased survival rate; the current study found a rate of mortality of 4% for this condition. However, a number of studies have reported a mortality rate of ≤10% (5,18).…”
Section: Discussionmentioning
confidence: 43%
“…This is in line with other reports. Palme et al reported that male sex, advanced initial stage, and presence of extra-thyroidal spread were independent predictors of multiple recurrences of DTC [23]. In a retrospective review of papillary micro-carcinoma (≤1cm), Mercante et al found that capsular invasion, extra-thyroidal tumor extension, and neck lymph node metastasis at presentation were the only independent risk factors for the persistence or recurrence of disease [24].…”
Section: Discussionmentioning
confidence: 99%